Controlled loading of paramagnetic gadolinium oxide nanoplates in PMAO-g-PEG as effective T1-weighted MRI contrast agents. Issue 15 (7th August 2014) - Yuan, Jiaquan; Peng, Erwin; Xue, Jun Min
Abstract: Abstract : Plate-shaped Gd2 O3 nanoclusters (GNCs) with well-controlled loading were fabricated by using amphiphilic poly(maleic anhydride-alt-1-octadecene) (PMAO) grafted with PEG as nanogel. The hydrodynamic size of the obtained GNCs was well controlled to <260 nm under appropriate emulsion process conditions and they showed excellent long-term dispersibility in phosphate buffer saline. MRI measurements clearly indicated the substantial improvement in T 1 effect of the nanoclusters as compared with the individual Gd2 O3 nanoplates. The obtained GNCs possessed a high r 1 value of 7.948 s −1 mM −1 [Gd], which is 2.23 times higher than that of the commercial product Gd-DOTA, and low r 2 / r 1 of 1.04. In vitro test of the obtained GNCs was demonstrated in NIH/3T3 cell lines, and clear T 1 -weighted images were obtained. Thus, the PMAO-g-PEG assisted GNCs were potentially useful for T 1 -weighted MRI contrast agents.